ADVANCE CARE PLANNING IN JAPANESE NURSING HOMES-USEFULNESS OF END-OF-LIFE CARE TEAM. Issue 2 (1st June 2013) - Nishikawa, M; Yokoe, Y; Kubokawa, N; Fukuda, K; Hattori, H; Yong-Jae, H; Miura, H; Endo, H; Nakashima, K
Abstract : Background: Although advance care planning (ACP) in nursing homes is important, the best means of promoting it in Japan remains to be clarified. Aim: The primary aim of this study, which was supported by trained ACP clinicians who are members of end-of-life care teams, was to clarify the usefulness of clinical strategies, such as a lecture about ACP and a multi-occupational interview regarding ACP in nursing homes. The secondary aim was to evaluate the quality of life (QOL) for families of residents who had died in nursing homes as per their wishes. Methods: Out of 108 families of nursing home residents, 59 participated in the lecture. Among the families of residents left the nursing home, we have conducted a multi-occupational interview with 14 families, and investigated the QOL for 13 bereaved families of residents who had died in nursing homes as per their wishes. Results: Out of 14 families of nursing home residents who received a multi-occupational interview, 13 residents died in the nursing home in accordance with the patient' wishes. Intervention by clinical strategies significantly increased the number of residents dying in nursing homes as per their wishes (p<0.01). The QOL of the bereaved was maintained. Discussion: The most important finding was that the residents' wishes were respected. Conclusion: Clinical strategies are more useful in promoting nursing home ACP.